STRATEGIC ADMINISTRATION AS A MANAGERIAL APPROACH AND IBGE MANAGEMENT IN THE 2022 CENSUS COLLECTION ARACAJU/SERGIPE AGENCY - de Oliveira Santos, Tatiane (Revista Gênero e Interdisciplinaridade, 2024)
Public administration has been restructuring itself over the last decades and adopting methodologies for modernizing public management. Thus, it has been disseminating strategic planning in its federal public institutions, consolidating a model of participatory management. Strategic management tools come to assist the strategic planning process, in the identification of problems and in the search for a solution, enabling the creation and execution of a work plan and implementation of public policies, in view of the government’s turnover. In this work, it will be presented how IBGE Aracaju-SE acted in the Strategic Planning and collection of the 2022 Demographic Census, and how the Strategic Management tools helped and contributed to the execution of the process and delivery of results.